An empirical analysis of the liquidity effect on corporate bond yield spreads - Shen, Chao (2017)
Using the sample which consists of 139 corporate bonds from the year 2010 to 2017, it is found that liquidity effect is significant in determining corporate yield spreads, in addition, lower liquidity is related to a higher yield spread. Two liquidity measures, the bid-ask spread and the percentage of zero returns, are employed. For each liquidity measure in different models, the findings hold the same, after controlling for other determinants referring to the financial situations of firms, bond characteristics, and information from the Treasury bond market. In comparison to the percentage of zero returns, bid-ask spread performs better in explaining yield spreads. And the majority of yield spreads is explained by credit quality. The results are robust after controlling for potential endogeneity bias. The paper extends the work of some previous studies by researching the Canadian corporate bond market and has significant implications for the corporate bond valuation.